Perlindungan Hukum bagi Pemegang Letter C Atas Tanah yang Diklaim Oleh Instansi Pemerintah - Mulat Mrabawani; Wanda Odelya Kusuma Atha; Brenda Aurora Taradwipa (International Forum of Researchers and Lecturers, 2026)
This study aims to analyse the legal status of physical possession evidenced by a Letter C under land law, as well as the issue of legal certainty in the resolution of land disputes by the state. Many members of the public still rely on a Letter C as proof of possession of the land they own, even though this document serves only as administrative evidence and not as a strong instrument of proof of ownership. This study employs a juridical-normative legal research method using a legislative approach and a conceptual approach. The legal materials were gathered through a literature review and analysed qualitatively, with the findings presented in a descriptive format. The results indicate that Letter C possesses relatively weak evidential weight as it is merely an administrative record that does not follow the procedures within the land registration system as stipulated by the UUPA. Currently, Letter C serves only as a guide and therefore no longer possesses legal force equivalent to a certificate. The land system in Indonesia adopts a negative publication system with a positive tendency, meaning that a certificate constitutes strong evidence of rights, but may still be revoked if another party is able to prove their rights.